The genre of piano concerto in the creativity of Carl Czerny - Stakhevych, Halyna (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2019)
Relevance of the study. The genre of the piano concerto of the first third of the 19 century — is one of the most interesting components of the piano concert heritage. It is a rather large stratum of piano literature, which today hasn’t received proper study. The innovations of the early romantic piano concerto are reflected in the works of pianists-composers of Austro-German music, among who is Carl Czerny, whose achievements have not received proper lighting yet. Scientific novelty. Czerny’s concerts are reviewed and analyzed for the first time, whose concert creativity has not been widely studied in Ukrainian musicology. Main objective. The purpose of the article is to consider the stylistic and compositional features of С. Czerny’s concert work and to determine its place in the piano concert art of the romantic era. Methodology. In order to reveal the peculiarities of С. Czerny’s composer style and to analyze his musical works, the methods of historical-comparative interpretation and theoretical generalization are used in this article. The discovery of stylistic peculiarities of piano concertos by С. Czerny, artistic-figurative content, structure, expressive and technical means, etc., was carried out with the help of musical-theoretical and performing analysis. Results. The most famous Austro-German piano composer of the first decades of the nineteenth century was Carl Czerny, whose creative work has not been adequately covered today. The artist created three concerts for piano and orchestra, which were created in the second half of the 1810s and 1820s. Turning to the innovations of C. Czerny in the concert genre, one must note the development of romantic traditions in the harmonious language, in particular, the strengthening of the lyrical and dramatic-pathetic beginnings of dramaturgy. In his works the diversity of the tonal coloration is noted, as well as the significant complication of the harmonic stratum. On the technical side, C. Czerny uses innovative techniques for the beginning of the 19 century, bringing to the brink of virtuosity the so-called “pearl” game. However, this did not lead to a compositional and dramaturgical disorder: all the concerts by C. Czerny are full of deep meaning and a truly sincere feeling, they are organic in the form and logic of musical development. Conclusions. Czerny’s piano concertos are a prime example of style changes, in which are tendencies of renewal of musical language, expansion of artistic means of expression (especially in the solo instrument parts), new compositional and textural solutions, a change in the ensemble ratio, etc. A deeper study of the creative heritage of Czerny will make it possible to trace the changes in musical thinking, which is most clearly expressed in the music of the first third of the 19 century. The concise analysis of concert art made in the article does not claim to be exhaustive and requires further study.